The Effect of Sleep Disturbances on the Severity of Depression in Psychiatric Patients: Pengaruh Gangguan Tidur terhadap Keparahan Depresi pada Pasien Psikiatri - Al-Showaily, Jaafar S; Saiwan, Marwa Jabbar (Indonesian Journal on Health Science and Medicine, 2025)
General Background :Depression and sleep disturbances are major global health challenges that often co-occur, each worsening the other and contributing to a high disease burden. Specific Background : While existing studies confirm their bidirectional relationship, limited evidence explores how specific sleep parameters independently influence depression severity. Knowledge Gap : Current research often treats sleep problems as a single construct, overlooking domain-specific contributions such as sleep duration, efficiency, and latency. Aims : This study aimed to assess the prevalence of sleep disturbances and measure their relationship with the severity of depression among psychiatric patients using the Pittsburgh Sleep Quality Index (PSQI) and Beck Depression Inventory-II (BDI-II). Results :In a cross-sectional analysis of 250 participants, 84% exhibited poor sleep quality and 92% displayed depressive symptoms, with 40% classified as severe. All PSQI domains showed significant correlations with BDI-II scores (p < 0.001), indicating a progressive relationship between deteriorating sleep and increasing depression severity. Novelty : This study provides comprehensive empirical evidence linking distinct sleep parameters to depression severity, highlighting that sleep quality deterioration parallels depression progression. Implications :These findings underscore the need for integrated interventions targeting both conditions and support routine sleep quality screening as a critical component of depression management and prevention strategies.Highlight : Most participants (84%) showed poor sleep quality with severe depression levels. There is a significant correlation between all sleep domains and depression severity. Improving sleep quality may help reduce depressive symptoms effectively. Keywords : Sleep Disturbances, Depression, Psychiatric Patients, Sleep Quality, PSQI